Determining the local communities’ livelihood resources in coastal and marine tourism destination development in Pangkor Island, Malaysia: preliminary findings - Ibrahim, Mohd Romzee; Masri, Noorhaiza; Mohd Hanafiah, Mohd Hafiz; Md Zain, Nur Adilah (Universiti Teknologi Mara, 2024)
Coastal and marine tourism development is best described as sustainable tourism as it helps in reducing socio-cultural and economic impacts towards the growth of a sustainable Blue Economy. Hence, a study on how tourism development effects the local communities’ livelihood resources has become a crucial factor within these contexts. This paper reports on a small pilot study to develop a set of community sustainable livelihoods in coastal and marine destination development in Pangkor Island, Perak, Malaysia. Local communities were surveyed to identify the indicator of their current living conditions they value most for the sustainable livelihood development of their communities. It seeks to determine the preliminary perceptions of local communities on the development of Pangkor Island in the context of their livelihood resources such as financial, social, human, physical, and natural assets. The pilot test sample size was 64 respondents, and random sampling techniques were utilized. It is hoped by developing this pilot test result will contributes to the establishment of a foundation for future sustainability in coastal and marine destination in Malaysia as well as offers beneficial implications to the industry practitioners.